GP126 Large deletions in DMD gene is the most prevalence mutation in russian children with duchenne muscular dystrophy. (June 2019) - Savostyanov, Kirill; Pushkov, Alexander; Kuzenkova, Ludmila; Zhurkova, Natalya; Nikitin, Alexey; Kurenkov, Alexey; Bursagova, Bella; Trufanov, Sergey
Abstract : Background and objectives: Duchenne muscular dystrophy (DMD) is a rare muscle disorder inherited by X-linked recessive type and affecting approximately 1 in 3, 500 male births worldwide. Patients and methods: The study included 63 boys, aged from 6 months to 8 years with elevated creatinine phosphokinase (CPK), according to laboratory tests. After medical genetic counseling molecular genetic analysis was performed for all patients. The MLPA method was used to search for deletions and duplications in the DMD gene, the analysis of point mutations was carried out by NGS, if the MLPA method did not reveal pathogenic variants. Sanger sequencing was used to validate mutations identified by the NGS. Results: Totally, in 39 patients we revealed different alterations in DMD gene. Among them 11 (28%) had a point mutations. It was 4 nonsense, 4 missense, 2 splicing mutation and one single-nucleotide duplication. Five mutation were novel. They are splicing c.10798–2A> G, missense c.2288T> A (p.Val763Asp) and c.3269A> T (p.Gln1090Leu), nonsense c.858T> G (p.Tyr286X) and duplication c.8325dup (p.Gln2776Thrfs*6) .The remaining 28 (72%) patients had gross duplications 3 (8%) and gross deletions 25 (64%) in the DMD gene. Interestingly, more than half of the patients had deletions in the region of exons 45–51 of the DMD gene. Conclusion: Our study showed that the most common cause of Duchenne dystrophy in Russian children are gross deletions of the DMD gene, in particular deletions in the region of exons 45–51 occurring most frequently.